(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The study aimed at detecting the effect of the use of Arabic language in teaching in reducing the use of the fifth grade students in the colloquial dialect in their class interaction in the classroom compared to the students who did not receive the teaching in fluent Arabic language, and to show the effect of the level of students’ achievement in Arabic language in their ability to use the language Arabic language in their interactions and responses within the classroom from the point of view of teachers according to the following variables: Independent variable: Teaching in Arabic without errors to the experimental group - Teaching to the control group is clear without errors and colloquial. - dependent variables: - levels of student achievement. - The responses of the fifth grade students (experimental - control). The researcher followed the experimental method and used the questionnaire to measure the degree of practice of the fifth grade teachers in the official schools in Damascus for fluent Arabic language from their point of view. - Note card to measure the degree of responses of pupils in both groups (experimental and control), and the tools were judged, and the calculation of its validity and stability. The sample number of students (101) students and students distributed in two sections of the study. (49) students and students (52 students) were randomly selected. The sample of primary education teachers was 120 teachers and was randomly withdrawn from the experimental schools. - The study reached the following results: - The teachers ’responses to the questionnaire items showed that the positive impact on teachers’ use of the Arabic language in teaching the fifth grade pupils in teaching their students to adhere to the Arabic language and reduce the slang in classroom interaction from the point of view of the teachers sample. Arabic language, and its role in the superiority of achievement in other subjects, and the study confirmed the commitment of teachers